Abonos orgánicos y microorganismos eficientes en el comportamiento agronómico del cultivo de nabo (Brassica napus l.) en el cantón La Maná - Rosero Zambrano, Faberh Javier (2013)
The present study was conducted in the La Maná canton, province of Cotopaxi, sector La Playita, is located between the coordinates geographical 00 ° 49' 00 "South latitude and 78 ° 48'30" West longitude. The experimental work lasted for three months. The treatments under study were as follows: T1 = organic fertilizer Agropesa (50L ha-1) Azotobacter spp. (1 L ha-1)T2 = manure organic Agropesa (50L ha-1) Pseudomonas fluorescens (1L ha-1) T3 = manure organic Biol (50L ha-1) Azotobacter spp. (1 L ha-1)T4 = manure organic Biol (50L ha-1) Pseudomonas fluorescens (1L ha-1) Was the Design of Completely Randomized Blocks (DBCA) with a total of four treatments and five replicates, with which was obtained 20 units experimentales. Results were: the largest average in treatments at 30 days the organic fertilizer Agropesa Azotobacter spp. reaches the 22.65 cm in height and 45 days the organic fertilizer Biol Pseudomonas fluorescens with 45.50 cm. In relation to the width of the leaves in greater volume to 30 days is given with organic fertilizer treatment Biol Pseudomona fluorescens with 8.72 cm. and 45 days the organic fertilizer Agropesa Azotobacter spp. with 16.55 cm. Determines the highest average length of sheet than organic manure treatment Agropesa Azotobacter spp. within 30 days has one height of 1940 cm and 45 days organic fertilizer biol Pseudomonas fluorescens with 43.40 cm. Corresponding to the treatment manure organic Biol Pseudomonas fluorescens with 57.71 cm in height at harvest. The variable yield per plot were recorded in treatment organic fertilizer Agropesa Azotobacter spp. with 5.72 tha-1